Evaluasi Tata Kelola Media Monitoring di Dinas Kebudayaan dan Pariwisata Kota Bandung - Muhammad Fatih; Saifullah Zakaria; Jovanscha Qisthy Adinda (LPPM Universitas Abdurrab, 2026)
This study aims to evaluate the governance of media monitoring at the Department of Culture and Tourism (Disbudpar) of Bandung City, focusing on the urgency of transitioning from manual to Artificial Intelligence (AI)-based digital systems. Within the UNDP good governance framework, effectiveness and responsiveness are the primary indicators analyzed. The research method employed is descriptive qualitative with a data triangulation approach through observation, documentation studies, and in-depth interviews with the Prodatin (Public Relations) team. The results indicate that manual data collection leads to time inefficiency and limited news coverage, causing significant public sentiments to be overlooked. Fundamental findings reveal that the implementation of AI-based automation tools is essential to expand the reach of real-time information. However, the effectiveness of this technology is highly dependent on enhancing human resource competence through technical training and the formalization of digital Standard Operating Procedures (SOP). This study concludes that the integration of AI technology, competent human resources, and standardized procedures is an absolute prerequisite for achieving accountable and responsive public communication in the digital era.